COMMUNITY EMPOWERMENT THROUGH WASTE BANKS IN MAMMI VILLAGE, BINUANG DISTRICT, POLEWALI MANDAR REGENCY - Nurlia, Nurlia; Guntur, Muhammad; Yamin, Muh Nur; Sulmiah, Sulmiah (Jurnal Aktor, 2025)
This research uses descriptive research methods with a qualitative approach. A qualitative approach is an approach that allows the discovery and understanding of the meaning of certain individuals or groups of people from social or humanitarian problems. The type of qualitative descriptive research used in this research is collecting information about the role of community empowerment in Mammi Village, Binuang District, Polewali Mandar Regency. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Triangulation is used to explain the validity of the data using source triangulation and technical triangulation.The research results show that in essence community empowerment is not forever, in other words community empowerment takes place through a learning process which is carried out in stages until the community achieves independence. The process for community empowerment will take place in stages. The programs that are being carried out so that the advanced TPS3R develops are the 3R (Reduce, Reuse and Recycle). By implementing the 3R principle, waste bank management in Mammi village will run in accordance with what the community in Mammi village expects.